Sinking krill carcasses as hotspots of microbial carbon and nitrogen cycling in the Arctic - Franco-Cisterna, Belén; Glud, Anni; Bristow, Laura A.; Rudra, Arka; Sanei, Hamed; Winding, Mie H.S.; Nielsen, Torkel G.; Glud, Ronnie N.; Stief, Peter (Frontiers in Marine Science, 2022)
Krill represent a major link between primary producers and higher trophic levels in polar marine food webs. Potential links to lower trophic levels, such as heterotrophic microorganisms, are less well documented. Here, we studied the kinetics of microbial degradation of sinking carcasses of two dominant krill species Thysanoessa raschii and Meganyctiphanes norvegica from Southwest Greenland. Degradation experiments under oxic conditions showed that 6.0-9.1 % of carbon and 6.4-7.1 % of nitrogen were lost from the carcasses after one week. Aerobic microbial respiration and the release of dissolved organic carbon were the main pathways of carbon loss from the carcasses. Ammonium release generally contributed the most to carcass nitrogen loss. Oxygen micro profiling revealed anoxic conditions inside krill carcasses/specimens, allowing anaerobic nitrogen cycling through denitrification and dissimilatory nitrate reduction to ammonium (DNRA). Denitrification rates were up to 5.3 and 127.7 nmol N carcass-1 d-1 for T. raschii and M. norvegica, respectively, making krill carcasses hotspots of nitrogen loss in the oxygenated water column of the fjord. Carcass-associated DNRA rates were up to 4-fold higher than denitrification rates, but the combined activity of these two anaerobic respiration processes did not contribute significantly to carbon loss from the carcasses. Living krill specimens did not harbor any significant denitrification and DNRA activity despite having an anoxic gut as revealed by micro profiling. The investigated krill carcasses sink fast (1500-3000 m d-1) and our data show that only a small fraction of the associated carbon is lost during descent. Based on data on krill distribution, our findings are used to discuss the potential importance of sinking krill carcasses for sustaining benthic food webs in the Arctic.